Species identification of biological ingredients in herbal product, Gurigumu-7, based on DNA barcoding and shotgun metagenomics - Wei, Miaojie; Tian, Yu; Zang, Erhuan; Tsambaa, Battseren; Liu, Jinxin; Shi, Linchun; Borjigidai, Almaz (Frontiers in Plant Science, 2024)
Accurate identification the species composition in mixtures poses a significant challenge, especially in processed mixtures comprising multiple species, such as those found in food and pharmaceuticals. Therefore, we have attempted to utilize shotgun metabarcoding technology to tackle this issue. In this study, the method was initially established using two mock samples of the Mongolian compound preparation Gurigumu-7 (G-7), which was then applied to three pharmaceutical products and 12 hospital-made preparations. A total of 119.72 Gb of raw data sets were obtained through shotgun metagenomic sequencing. By combining ITS2, matK, and rbcL, all the labeled bio-ingredients specified in the G-7 prescription can be detected, although some species may not be detectable in all samples. The prevalent substitution of Akebia quinata can be found in all the pharmaceutical and hospital samples, except for YN02 and YN12. The toxic alternative to Akebia quinata, Aristolochia manshuriensis, was exclusively identified in the YN02 sample. To further confirm this result, we validated it in YN02 using HPLC and real-time PCR with TaqMan probes. The results showed that aristolochic acid A (AAA) was detected in YN02 using HPLC, and the ITS2 sequence of Aristolochia manshuriensis has been validated in YN02 through qPCR and the use of a TaqMan probe. This study confirms that shotgun metabarcoding can effectively identify the biological components in Mongolian medicine compound preparation G-7. It also demonstrates the method's potential to be utilized as a general identification technique for mixtures containing a variety of plants.